2009
DOI: 10.1021/mp800215d
|View full text |Cite
|
Sign up to set email alerts
|

Lipoplexes Targeting the CD44 Hyaluronic Acid Receptor for Efficient Transfection of Breast Cancer Cells

Abstract: Lipoplexes containing a hyaluronic acid-dioleoylphosphatidylethanolamine (HA-DOPE) conjugate were designed to target the CD44 receptor on breast cancer cells. Cationic liposomes composed of a mixture of [2-(2,3-didodecyloxypropyl)hydroxyethyl]ammonium bromide (DE) and dioleoylphosphatidylethanolamine (DOPE) with or without HA-DOPE were prepared, characterized, and used to form a complex with plasmid DNA pCMV-luc. Lipoplexes displayed a negative zeta potential and a mean diameter between 250-300 nm. Cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 46 publications
4
110
0
Order By: Relevance
“…Previous studies by Surace et al [17] have shown that 10% HA-DOPE (w/w) was optimal for transfection of MDA-MB231 breast cancer cells expressing CD44. We have therefore used this amount of conjugate and formulated lipoplexes at different lipids:DNA ratios.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies by Surace et al [17] have shown that 10% HA-DOPE (w/w) was optimal for transfection of MDA-MB231 breast cancer cells expressing CD44. We have therefore used this amount of conjugate and formulated lipoplexes at different lipids:DNA ratios.…”
Section: Discussionmentioning
confidence: 96%
“…We have synthesized a HA-DOPE conjugate which was included in lipoplexes demonstrating an improved transfection of breast cancer cells when these cells express the CD44 receptor [17]. These first results have demonstrated that using HA was indeed relevant for increasing the expression of a reporter gene in a cancer cell line.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Optimization of the molecular weight of HA, and the use of a pH sensitive cationic lipid are some promising candidates. Other groups demonstrated that liposomes containing a HA-DOPE lipid conjugate had targeting ability for CD44 expressed cells in vitro, 20,21) however, these studies were only evaluated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its moisturizing properties, hyaluronic acid (HA) and its endogenous receptor cluster of differentiation CD 44 , a transmembrane glycoprotein, have been linked to tumor growth, invasion, and metastasis. 21 Drug delivery systems have been developed to combine the specificity of the HA/CD 44 interaction with their respective carrier and targeting functions. 22,23 MSN has good potential as a carrier for drug delivery due to its mesoporous structure, high specific surface area, biocompatibility, and high DL capacity.…”
Section: Introductionmentioning
confidence: 99%